Lignocellulose processing: a current challenge - Singhvi, Mamata S.; Chaudhari, Shivani; Gokhale, Digambar V. (RSC Advances, 2014)
Lignocellulosic biomass, of which inedible crops are a renewable source, is expected to become one of the key renewable energy resources in the near future, to deal with global warming and the depletion of conventional fossil fuel resources. It also holds the key to supplying society's basic needs for the sustainable production of chemicals and fuels without impacting the human food supply. Despite this, the production of 2nd generation biofuels and chemicals has not yet been commercialized. Therefore, the challenges involved in the production of lignocellulosic biomass derived fuels and chemicals must be addressed. The search for economic pretreatment methods has been recognized as one of the main hurdles for the processing of biomass to biofuels and chemicals. The conversion of all biomass components, lignin in particular, would greatly contribute to the economic viability of biomass based processes for 2nd generation biofuels and chemicals. The highly organized crystalline structure of cellulose presents an obstacle to its hydrolysis. Hydrolysis of lignocellulose carbohydrates into fermentable sugars requires a number of different biomass degrading enzymes such as cellulases and hemicellulases. Still, a number of technical and scientific issues within pretreatment and hydrolysis remain to be solved. Depending on the raw material and pretreatment technology, the enzyme mixtures must be designed to degrade biomass carbohydrates. Rapid advances in enzyme, microbial and plant engineering would provide the necessary breakthroughs for the successful commercialization of biomass derived fuels and chemicals.

Biomass exploitation - a challenge finding its way to reality - Singhvi, Mamata S.; Gokhale, Digambar V. (Current Science, 2015)
Lignocellulosic biomass holds the key to supplying the basic needs of society for sustainable production of chemicals and fuels without impacting the human food supply. The production of second-generation biofuels and chemicals from lignocellulosic biomass has not yet been commercialized due to its complex and recalcitrance structure. Therefore, the challenges involved in the production of lignocellulosic biomass-derived fuels and chemicals must be addressed. Search for economic pretreatment methods has been recognized as one of the main hurdles for processing of biomass to biofuels and chemicals. The conversion of all biomass components, lignin in particular, would greatly contribute to the economic viability of biomass-based processes for second-generation biofuels and chemicals. Hydrolysis of lignocellulose carbohydrates into fermentable sugars requires a suitable cellulase enzyme cocktail acting on both raw as well as pretreated biomass. Depending on raw material and pretreatment technology, the enzyme mixtures must be designed to degrade biomass carbohydrates. Recent publications on GVL-pretreatment to solubilize and degrade carbohydrates in biomass and CelA enzyme acting on raw biomass would probably meet the challenges in biomass conversion technologies.

Stimulation of d - and l -lactate dehydrogenases transcriptional levels in presence of diammonium hydrogen phosphate resulting to enhanced lactic acid production by Lactobacillus strain - Singhvi, Mamata S.; Zendo, Takeshi; Iida, Hiroshi; Gokhale, Digambar V.; Sonomoto, Kenji (Journal of Bioscience and Bioengineering, 2017)
The present study revealed the effect of nitrogen sources on lactic acid production and stimulation of d- and l-lactate dehydrogenases (LDH) of parent Lactobacillus lactis NCIM 2368 and its mutant RM2-24 generated after UV mutagenesis. Both the parent and mutant strains were evaluated for d-lactic acid production in control and modified media. The modified media did not show remarkable effect on lactic acid production in case of parent whereas mutant exhibited significant enhancement in d-lactic acid production along with the appearance of l-lactic acid in the broth. Both LDH activities and specific activities were found to be higher in mutant than the parent strain. These results suggested that the diammonium hydrogen phosphate in modified media triggered the expression of LDH genes leading to enhanced lactic acid production. This observation has been proved by studying the expression levels of d- and l-LDH genes of parent and mutant in control and modified media using quantitative RT-PCR technique. In case of mutant, the transcriptional levels of d-LDH and l-LDH increased ∼17 fold and ∼1.38 fold respectively in modified medium compared to the values obtained with control medium. In case of parent, no significant change in transcriptional levels of d- and l-LDH was found when the cells were grown in either control medium or modified medium. This study suggested that the mutant, RM2-24 has l-LDH gene which is expressed in presence of (NH4)2HPO4 resulting in l-lactic acid production. Co-production of l-lactic acid in d-lactic acid fermentation may be detrimental in the PLA production.

Greener L-lactic acid production through in situ extractive fermentation by an acid-tolerant Lactobacillus strain - Singhvi, Mamata S.; Zendo, Takeshi; Gokhale, Digambar; Sonomoto, Kenji (Applied Microbiology and Biotechnology, 2018)
Lactic acid (LA) fermentation requires a neutralizer for a physiologically acceptable range. However, a neutralizer generates a large amount of gypsum, an environmental pollutant. Furthermore, the downstream processing is complicated and expensive, comprising 50–70% of the total cost. We previously developed a Lactobacillus delbrueckii FM1, which can produce undissociated LA without neutralizer. Here, we improved FM1 by adaptive evolution at pH 4.5, which generated Adp FM1 showing an ~ 1.80-fold increase in LA production compared to FM1. The LA production via fed-batch fermentation yielded 36.2 g/L of LA, with a productivity of 0.500 g/L/h. However, cell viability was reduced due to the acidic pH and/or end-product inhibition. Therefore, an in situ LA recovery process using an extractive solvent was employed to maintain cell viability. Adp FM1 produced 49.2 g/L of LA via in situ LA-extractive fed-batch fermentation, which was ~ 1.4-fold higher than that without LA extraction. Adp FM1 provided a total LA productivity of 0.512 g/L/h in 96 h. Among the tested strains, Adp FM1 exhibited the highest H⁺-ATPase activity and a 415-fold increase in H⁺-ATPase gene expression compared to the parent strain. These results suggest that the in situ LA extractive fermentation process will ease downstream processing and prove to be a more economical and environmentally friendly option compared to the present fermentation. To our knowledge, this is the first report on the production of undissociated L-LA by Lactobacillus using an in situ recovery process, with high LA production levels and productivity.

Lignocellulosic biomass: hurdles and challenges in its valorization - Singhvi, Mamata S.; Gokhale, Digambar V. (Applied Microbiology and Biotechnology, 2019)
Lignocellulosic biomass (LCB) is globally available and sustainable feedstock containing sugar-rich platform that can be converted to biofuels and specialty products through appropriate processing. This review focuses on the efforts required for the development of sustainable and economically viable lignocellulosic biorefinery to produce carbon neutral biofuels along with the specialty chemicals. Sustainable biomass processing is a global challenge that requires the fulfillment of fundamental demands concerning economic efficiency, environmental compatibility, and social responsibility. The key technical challenges in continuous biomass supply and the biological routes for its saccharification with high yields of sugar sources have not been addressed in research programs dealing with biomass processing. Though many R&D endeavors have directed towards biomass valorization over several decades, the integrated production of biofuels and chemicals still needs optimization from both technical and economical perspectives. None of the current pretreatment methods has advantages over others since their outcomes depend on the type of feedstock, downstream process configuration, and many other factors. Consolidated bio-processing (CBP) involves the use of single or consortium of microbes to deconstruct biomass without pretreatment. The use of new genetic engineering tools for natively cellulolytic microbes would make the CBP process low cost and ecologically friendly. Issues arising with chemical characteristics and rigidity of the biomass structure can be a setback for its viability for biofuel conversion. Integration of functional genomics and system biology with synthetic biology and metabolic engineering undoubtedly led to generation of efficient microbial systems, albeit with limited commercial potential. These efficient microbial systems with new metabolic routes can be exploited for production of commodity chemicals from all the three components of biomass. This paper provides an overview of the challenges that are faced by the processes converting LCB to commodity chemicals with special reference to biofuels.
Keywords: Biomass pretreatment; Biomass supply chain; Cellulosic ethanol; Consolidated bio-processing; Lignocellulosic biomass (LCB)